Dissecting Drug-Induced Cytotoxicity and Metabolic Dysfunction in Conditionally Immortalized Human Proximal Tubule Cells - Hoogstraten, Charlotte A.; Smeitink, Jan A. M.; Russel, Frans G. M.; Schirris, Tom J. J. (Frontiers in Toxicology, 2022)
Fourteen to 26 percent of all hospitalized cases of acute kidney injury are explained by drug-induced toxicity, emphasizing the importance of proper strategies to pre-clinically assess renal toxicity. The MTT assay is widely used as a measure of cell viability, but largely depends on cellular metabolic activity. Consequently, MTT as a single assay may not be the best way to assess cytotoxicity of compounds that reduce mitochondrial function and cellular metabolic activity without directly affecting cell viability. Accordingly, we aim to highlight the limitations of MTT alone in assessing renal toxicity of compounds that interfere with metabolic activity. Therefore, we compared toxic effects observed by MTT with a fluorescent assay that determines compromised plasma membrane permeability. Exposure of proximal tubule epithelial cells to nephrotoxic compounds reduced cellular metabolic activity dose- and time-dependently. We show that compared to our fluorescence-based approach, assessment of cellular metabolic activity by means of MTT provides a composite readout of cell death and metabolic impairment. An approach independent of cellular metabolism is thus preferable when assessing cytotoxicity of compounds that induce metabolic dysfunction. Moreover, combining both assays during drug development enables a first discrimination between compounds having a direct or indirect mitochondrial toxic potential.